Hydrogen transport hose and manufacturing method for the same

By using a combination of thermoplastic resin with high light transmittance and low haze in the inner layer of the hydrogen transportation pipeline, and removing large particles through optical detection, the problem of reduced fatigue durability during high-pressure transportation in low temperature environments is solved, and the efficient durability of the pipeline is improved.

JP2025065802APending Publication Date: 2025-04-22THE YOKOHAMA RUBBER CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023175253
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-10
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

When hydrogen transportation pipelines transport hydrogen at high pressure under low temperature environments, they are prone to decrease fatigue durability due to repeated deformation.

Method used

A thermoplastic resin combination material with high light transmittance and low haze is used as the inner layer material, and particles with a diameter of 0.7 mm or more are removed by optical detection to improve the fatigue durability of the pipe.

Benefits of technology

It significantly improves the fatigue durability of hydrogen transportation pipelines and ensures that the pipeline can maintain stable performance when transporting hydrogen at high pressure under low temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025065802000001_ABST
    Figure 2025065802000001_ABST
Patent Text Reader

Abstract

To provide a hydrogen transport hose.SOLUTION: A hydrogen transport hose includes an inner layer, a reinforcement layer, and an outer layer in this order. In the hydrogen transport hose, the inner layer includes a thermoplastic resin composition that comprises thermoplastic resin and elastomer and that has 60% or more of total light transmittance in a plate-like molded body with 1.0 mm of thickness measured in accordance with JIS K7361-1:1997, and has no particles with 0.7 mm or longer of a major axis when observed by emitting light from a D65 light source.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a hose for transporting hydrogen and a method for manufacturing the same. [Background technology]

[0002] In recent years, the development of fuel cell vehicles and the like has been actively promoted. Accordingly, the development of hydrogen transport hoses, such as hoses that transport hydrogen gas from dispensers installed at hydrogen stations to fuel cell vehicles and the like, is also progressing. Hydrogen transport hoses are required to have hydrogen gas barrier properties, flexibility in low-temperature environments, durability, and the like.

[0003] Patent Document 1 discloses a hydrogen transport component having a hydrogen gas barrier layer made of a resin composition containing polyamide 11 and a modified olefin-based elastomer, a reinforcing layer disposed on the outside of the hydrogen gas barrier layer, and an outer cover layer containing a polyamide resin disposed on the outside of the reinforcing layer, wherein the content of the modified olefin-based elastomer in the resin composition is 15% by mass to 50% by mass with respect to the total of the polyamide 11 and the modified olefin-based elastomer, and the resin composition is substantially free of plasticizer. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2018 / 155491 Summary of the Invention [Problem to be solved by the invention]

[0005] Hydrogen transport hoses are sometimes used to transport low-temperature hydrogen at high pressure. In such use, the hydrogen transport hoses may be repeatedly deformed while being cooled by low-temperature hydrogen. Therefore, it is desirable to improve the fatigue durability of the tubes constituting the inner layer of the hydrogen transport hoses.

[0006] An object of the present disclosure is to provide a hose for transporting hydrogen having improved fatigue durability and a method for manufacturing the same. [Means for solving the problem]

[0007] The present inventors have found that the above object can be achieved by the following means: [Aspect 1] A hose for transporting hydrogen, comprising an inner layer, a reinforcing layer, and an outer layer in this order, The inner layer is The thermoplastic resin composition is made of a thermoplastic resin and an elastomer, and has a total light transmittance of 60% or more in a plate-shaped molded product having a thickness of 1.0 mm as measured in accordance with JIS K7361-1:1997; and When observed under light of D65 light source, it does not have particles with a major axis of 0.7 mm or more. A hose for transporting hydrogen, comprising: [Aspect 2] 2. The hose for transporting hydrogen according to aspect 1, wherein the thermoplastic resin composition has a haze of 90% or less in a plate-shaped molded product having a thickness of 1.0 mm, as measured in accordance with JIS K7136:2000. [Aspect 3] 3. The hose for transporting hydrogen according to claim 1 or 2, wherein the thermoplastic resin composition has an islands-in-a-sea structure in which the thermoplastic resin is a matrix and the elastomer is a domain. [Aspect 4] 4. The hose for transporting hydrogen according to claim 3, wherein the domains have a number average particle size of 1.0 μm or less. [Aspect 5] 3. The hose for transporting hydrogen according to aspect 1 or 2, wherein the elastomer is a modified styrene-based thermoplastic elastomer having a styrene ratio of 15 to 50 mol %. [Aspect 6] Aspect 6. The hose for transporting hydrogen according to aspect 5, wherein the modified styrene-based thermoplastic elastomer is acid-modified and has an acid value of 1 to 15 mgCH3ONa / g. [Aspect 7] 3. The hose for transporting hydrogen according to claim 1 or 2, wherein 50% by mass or more of the thermoplastic resin is polyamide 11 or polyamide 12. [Aspect 8] The oxygen permeability coefficient of the thermoplastic resin composition at 21°C and 0% RH, as measured in accordance with ASTM D3985, is 0.005 to 0.100 mm cc / (m 2 3. The hose for transporting hydrogen according to claim 1 or 2, wherein the hydrogen transport resistance is 1.0·day·mmHg. [Aspect 9] A method for producing a hose for transporting hydrogen, the hose having an inner layer, a reinforcing layer, and an outer layer in this order, comprising the steps of: Molding an inner layer precursor containing a thermoplastic resin composition that contains a thermoplastic resin and an elastomer and has a total light transmittance of 60% or more in a plate-shaped molded product having a thickness of 1.0 mm as measured in accordance with JIS K7361-1:1997; inspecting the inner layer precursor for the presence or absence of particles having a major axis of 0.7 mm or more by a light inspection performed by irradiating the inner layer precursor with light from a D65 light source; removing said particles, if present, from said inner layer precursor; A method for producing a hose for transporting hydrogen, comprising the steps of: Effect of the Invention

[0008] According to the present disclosure, it is possible to provide a hose for transporting hydrogen having improved fatigue durability and a method for manufacturing the same. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a partially cutaway perspective view of a hose 1 for transporting hydrogen according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, embodiments of the present disclosure will be described in detail. Note that the present disclosure is not limited to the following embodiments, and various modifications can be made within the scope of the present disclosure.

[0011] <Hydrogen transport hose> The hose for transporting hydrogen of the present invention is a hose for transporting hydrogen having, in this order, an inner layer, a reinforcing layer, and an outer layer, wherein the inner layer comprises a thermoplastic resin composition which is made of a thermoplastic resin and an elastomer, and which has a total light transmittance of 60% or more in a plate-shaped molded product having a thickness of 1.0 mm as measured in accordance with JIS K7361-1:1997, and which does not contain any particles whose longest possible length, i.e., whose major axis, is 0.7 mm or more when observed by irradiating it with light from a D65 light source.

[0012] A resin composition (alloy) containing a resin and an elastomer is suitable as a material for the tube constituting the inner layer of the hydrogen transport hose of the present invention. However, when such a resin composition is used to mold a tube as the inner layer, large particles such as gel particles and retained particles may be formed during kneading or extrusion of the resin composition. If such large particles are present in the inner layer, there is a risk that the particles may become the starting point for failure, that is, the fatigue durability of the inner layer may be reduced.

[0013] Therefore, it is desirable that the inner layer of a hydrogen transport hose contains few such large particles, and it is desirable to detect and remove such particles from the inner layer, for example, during production.

[0014] Possible methods for detecting such large particles include X-ray CT inspection and optical inspection. Here, large-scale equipment is required to perform X-ray CT inspection on the inner layer precursor, such as a tube, formed in the manufacturing process of a hydrogen transport hose. Therefore, optical inspection is more realistic. However, resin compositions (alloys) containing resin and elastomer are generally cloudy and have low transparency, making it difficult to detect large particles by optical inspection.

[0015] In the hydrogen transport hose of the present invention, a thermoplastic resin composition having a total light transmittance of 60% or more in a plate-shaped molded product having a thickness of 1.0 mm measured according to JIS K7361-1:1997 is used for the inner layer. Therefore, the inner layer of the hydrogen transport hose is less cloudy, and for example, in a light inspection performed by irradiating the inner layer or the inner layer precursor with light from a D65 light source during the manufacturing process, large particles, specifically particles with a major axis of 0.7 mm or more, can be easily detected. Therefore, by performing a light inspection during the manufacturing process and removing the particles from the inner layer, the large particles in the inner layer of the hydrogen transport hose can be reduced. In the hydrogen transport hose of the present invention, particles with a major axis of 0.7 mm or more are detected and removed from the inner layer during, for example, a light inspection during the manufacturing process, and therefore, when the inner layer is irradiated with light from a D65 light source and observed, there are no particles with a major axis of 0.7 mm or more. In other words, when the inner layer is irradiated with light from a D65 light source and observed, particles with a major axis of 0.7 mm or more are not observed with the naked eye.

[0016] As a result, the hydrogen transport hose of the present invention has high fatigue durability.

[0017] 1 is a perspective view of a hydrogen transport hose 1 according to an embodiment of the present invention, with a portion cut away to clearly show the layer structure, although the present invention is not limited to what is shown in the drawing.

[0018] The hydrogen transport hose 1 has an inner layer 2, a reinforcing layer 3, and an outer layer 4 in this order. That is, the reinforcing layer 3 is disposed outside the inner layer 2, and the outer layer 4 is disposed outside the reinforcing layer 3. Although not shown in FIG. 1, the inner layer 2 contains a thermoplastic resin composition made of a thermoplastic resin and an elastomer. Here, the thermoplastic resin composition has a total light transmittance of 60% or more in a plate-shaped molded product having a thickness of 1.0 mm measured according to JIS K7361-1:1997. The inner layer 2 does not contain particles having a major axis of 0.7 mm or more when observed by irradiating it with light from a D65 light source.

[0019] In Fig. 1, the reinforcing layer 3 has three layers 5 made of organic fibers, and one layer 6 made of metal wire outside the layers 5 made of organic fibers. However, Fig. 1 does not limit the configuration of the reinforcing layer 3 of the hose for transporting hydrogen of the present invention.

[0020] <Inner layer> The inner layer contains a thermoplastic resin composition consisting of a thermoplastic resin and an elastomer.

[0021] (Thermoplastic resin composition) The thermoplastic resin composition comprises a thermoplastic resin and an elastomer.

[0022] The elastomer used in the thermoplastic resin composition is not limited as long as the thermoplastic resin composition has a desired total light transmittance, and examples thereof include styrene-based thermoplastic elastomers.

[0023] Styrenic thermoplastic elastomers are block copolymers that use polystyrene as the hard segment and polydiene as the soft segment. Examples of styrenic thermoplastic elastomers include styrene-butadiene-styrene block copolymers (SBS), styrene-ethylene-butylene-styrene block copolymers (SEBS), styrene-isoprene-styrene block copolymers (SIS), styrene-isobutylene-styrene block copolymers (SIBS), styrene-ethylene-propylene block copolymers (SEP), styrene-ethylene-propylene-styrene block copolymers (SEPS), and modified products thereof, such as acid-modified products, amine-modified products, or epoxy-modified products.

[0024] The elastomer is preferably a modified product of a styrene-based thermoplastic elastomer, i.e., a modified styrene-based thermoplastic elastomer, and more preferably a modified styrene-based thermoplastic elastomer having a styrene ratio of 15 to 50 mol %. A thermoplastic resin composition using such an elastomer has a high total light transmittance.

[0025] Among modified styrene-based thermoplastic elastomers, those that are acid-modified and have an acid value of 1 to 15 mgCH3ONa / g are more preferred. Thermoplastic resin compositions using such elastomers have low haze and excellent fatigue durability. When the haze is not high, the detection accuracy of large particles by light testing can be improved, and therefore the number of large particles in the inner layer can be reduced.

[0026] The thermoplastic resin used in the thermoplastic resin composition may be, for example, polyamide, polyester, ethylene-vinyl alcohol copolymer resin, polyacetal, modified polyphenylene ether, polyketone, or polyphenylene sulfide.

[0027] Examples of polyamides include polyamide 6, polyamide 66, polyamide 6 / 66 copolymer, polyamide 11, polyamide 12, polyamide 610, polyamide 612, polyamide 46, polyamide 410, polyamide 1010, polyamide 1012, polyamide MXD6, polyamide 6T, polyamide 9T, polyamide 10T, and polyamide 11 / 10T.

[0028] It is preferable that 50% by mass or more of the thermoplastic resin used in the thermoplastic resin composition is polyamide 11 or polyamide 12. A thermoplastic resin composition using such a thermoplastic resin has high total light transmittance.

[0029] The thermoplastic resin composition preferably has a sea-island structure in which the thermoplastic resin is the matrix and the elastomer is the domain. A thermoplastic resin composition having such a structure has both high gas barrier properties and high fatigue durability.

[0030] In the islands-in-the-sea structure, the number average particle size of the elastomer domains may be, for example, 2.0 μm or less or more than 0.0 μm. The number average particle size of the domains may be 2.0 μm or less, 1.8 μm or less, 1.6 μm or less, 1.4 μm or less, 1.2 μm or less, 1.0 μm or less, 0.8 μm or less, 0.6 μm or less, 0.4 μm or less, or 0.2 μm or less. The number average particle size of the domains may be more than 0.0 μm, 0.1 μm or more, 0.2 μm or more, 0.3 μm or more, 0.4 μm or more, or 0.5 μm or more.

[0031] The number average particle size of the domains is preferably 1.0 μm or less. If the particle size of the elastomer domains is small, the total light transmittance can be improved.

[0032] The number-average particle size of the domains can be determined by, for example, cutting the tube constituting the inner layer with a razor to expose a surface perpendicular to the longitudinal direction of the tube, cooling it with liquid nitrogen, creating a smooth surface with a diamond knife, and using an atomic force microscope AFM MFP3D manufactured by Asylum Research to obtain a phase image in tapping mode with contrast between the matrix and the domains, binarizing the obtained image, and then performing particle analysis on approximately 500 domains using image analysis software. The image analysis software can be a tool provided with the AFM or general-purpose software such as ImageJ, and the binarization process can be performed by creating a histogram of the number of pixels appearing versus the phase, and then using the phase at the boundary between the matrix and the domain as a threshold value.

[0033] The thermoplastic resin composition has an oxygen permeability coefficient of 0.005 to 0.100 mm cc / (m at 21°C and 0% RH as measured in accordance with ASTM D3985. 2 When the oxygen permeability coefficient is in this range, the hydrogen permeation amount of the hydrogen transport hose is particularly low, which is desirable. The oxygen permeability coefficient is preferably 0.100 mm cc / (m 2 ·day·mmHg) or less, 0.050mm·cc / (m 2·day·mmHg) or less, 0.040mm·cc / (m 2 ·day·mmHg) or less, 0.030mm·cc / (m 2 ·day·mmHg) or less, 0.020mm·cc / (m 2 ·day·mmHg) or less, or 0.010mm·cc / (m 2 ·day·mmHg or less.

[0034] (Total light transmittance) The thermoplastic resin composition has a total light transmittance of 60% or more in a plate-shaped molded product having a thickness of 1.0 mm, measured according to JIS K7361-1: 1997. When an inner layer is molded using a thermoplastic resin composition having a total light transmittance of 60% or more, a larger number of large particles, i.e., particles having a major axis of 0.7 mm or more, can be detected and removed in an optical inspection of the inner layer.

[0035] The total light transmittance may be 60% or more, 62% or more, 63% or more, 64% or more, 65% or more, or 70% or more.

[0036] Here, the total light transmittance can be measured by forming the thermoplastic resin composition into a plate-shaped molded product, for example, a sheet, having an average thickness of 1.0 mm, and measuring it according to JIS K7361-1:1997 using a turbidity meter NDH2000 manufactured by Nippon Denshoku Industries Co., Ltd., at 23°C, with a light source of D65, a measuring diameter of 20 mm, and a single beam method. The method for measuring the average thickness is not particularly limited, but a general contact or non-contact thickness measuring method can be used, and among them, a micrometer or a stylus thickness meter is preferred. The average thickness is preferably the arithmetic average of thicknesses measured at three or more points within the area through which light passes.

[0037] (Haze) The thermoplastic resin composition preferably has a haze of 90% or less in a plate-shaped molded product having a thickness of 1.0 mm measured according to JIS K7136: 2000. When an inner layer is molded using a thermoplastic resin composition having a haze of 90% or less, particles having a major axis of 0.7 mm or more are more easily detected in an optical inspection of the inner layer, and therefore more particles having a major axis of 0.7 mm or more can be detected and removed in the optical inspection.

[0038] The haze may be 90% or less, 80% or less, 70% or less, 60% or less, or 50% or less.

[0039] Here, the haze can be measured by molding the thermoplastic resin composition into a plate-like molded product, for example a sheet, having an average thickness of 1.0 mm, and measuring the haze in accordance with JIS K7136:2000 using a turbidity meter NDH2000 manufactured by Nippon Denshoku Industries Co., Ltd. at 23°C, a light source D65, a measuring diameter of 20 mm, and a single beam method.

[0040] (Optical Inspection) The inner layer does not contain particles with a major axis of 0.7 mm or more in an optical inspection in which light from a D65 light source is irradiated and observed. Optical inspection can be performed by irradiating the inner layer of the hydrogen transport hose with light from a D65 light source and observing the presence or absence of particles with a major axis of 0.7 mm or more. Optical inspection can be performed, for example, by separating the inner layer from the hydrogen transport hose.

[0041] <Reinforcing layer> The reinforcing layer is a layer provided between the inner layer and the outer layer, and may be composed of, for example, a braided layer or a spiral layer formed by braiding organic fibers or metal wires. Examples of the organic fibers include polyparaphenylene benzbisoxazole (PBO) fibers, aramid fibers, and carbon fibers, with PBO fibers being preferred. The wire diameter of the organic fibers is preferably 0.25 to 0.30 mm. Examples of the metal wires include steel wires, copper and copper alloy wires, aluminum and aluminum alloy wires, magnesium alloy wires, titanium and titanium alloy wires, with steel wires being preferred. The wire diameter of the metal wires is preferably 0.25 to 0.40 mm.

[0042] The reinforcing layer of the hydrogen transport hose of the present invention is not particularly limited, and may include, for example, at least one layer made of organic fiber. As shown in Figure 1, the hydrogen transport hose of the present invention preferably includes three layers made of organic fiber and further includes one layer made of metal wire on the outside.

[0043] <Outer layer> The material constituting the outer layer is not limited to a thermoplastic elastomer, vulcanized rubber, etc., and is preferably a thermoplastic elastomer. The thermoplastic elastomer is not limited to a polyester elastomer, a polyamide elastomer, or a polyurethane elastomer.

[0044] The thickness of the outer layer is not limited as long as the effects of the present invention are achieved, but it is preferably 0.2 to 1.2 mm, more preferably 0.3 to 1.0 mm, and even more preferably 0.4 to 0.8 mm.

[0045] <<Method of manufacturing a hose for transporting hydrogen>> The method for producing a hose for transporting hydrogen of the present invention includes the following steps: (A) molding an inner layer precursor containing a thermoplastic resin composition which contains a thermoplastic resin and an elastomer, and in a plate-shaped molded product having a thickness of 1.0 mm, the total light transmittance measured in accordance with JIS K7361-1:1997 is 60% or more; (B) inspecting the inner layer precursor for the presence or absence of particles having a major axis of 0.7 mm or more by a light inspection performed by irradiating the inner layer precursor with light from a D65 light source; and (C) removing particles, if present, from the inner layer precursor;

[0046] In the above step (A), the thermoplastic resin composition can be extruded into a tube shape by extrusion molding to form an inner layer precursor. In addition, in the above step (C), for example, the part of the inner layer precursor where particles having a major axis of 0.7 mm or more are present can be cut in the radial direction of the tube and removed. The reinforcing layer and the outer layer can be formed, for example, by braiding fibers to be the reinforcing layer on the outside of the inner layer precursor, and further covering the fibers with the outer layer (outer tube) by extrusion molding. EXAMPLES

[0047] Examples 1 to 13 and Comparative Examples 1 to 4 <Raw materials> The following ingredients were used in the amounts shown in Tables 1-1 and 1-2 to form the sheets. (thermoplastic resin) PA11: Polyamide 11 "RILSAN" (registered trademark) BESN OTL manufactured by Arkema PA12: UBE Corporation Polyamide 12 "UBESTA" (registered trademark) 3020U PA1010: Polyamide 1010 "VESTAMID" (registered trademark) Terra DS16 manufactured by Polypla Evonik Co., Ltd. PA6.66: UBE Corporation polyamide 6 / 66 copolymer "UBE NYLON" (registered trademark) 5023B (Elastomer) MahEBR: Maleic anhydride modified ethylene-1-butene copolymer "Tafmer" (registered trademark) MH7020 manufactured by Mitsui Chemicals, Inc. MahSEBS-1: Maleic anhydride modified styrene-ethylene-butylene-styrene block copolymer "TUFTECH" (registered trademark) M1913 manufactured by Asahi Kasei Corporation Acid value 10mgCH3ONa / g, styrene ratio 30mol% MahSEBS-2: A 50:50 blend by weight of Asahi Kasei Corporation's maleic anhydride-modified styrene-ethylene butylene-styrene block copolymer "TUFTECH" (registered trademark) M1913 and maleic anhydride-modified styrene-ethylene butylene-styrene block copolymer "TUFTECH" (registered trademark) M1911 (acid value 2 mgCH3ONa / g, styrene ratio 30 mol%) (average acid value 6 mgCH3ONa / g). MahSEBS-3: A 50:50 blend by weight of Asahi Kasei Corporation's styrene-ethylene-butylene-styrene block copolymer "TUFTECH" (registered trademark) H1043 (acid value 0 mgCH3ONa / g, styrene ratio 67 mol%) and Asahi Kasei Corporation's maleic anhydride-modified styrene-ethylene-butylene-styrene block copolymer "TUFTECH" (registered trademark) M1913 (acid value 10 mgCH3ONa / g, styrene ratio 30 mol%) (average acid value 5 mgCH3ONa / g, average styrene ratio 49 mol%) MahSEBS-4: A 50:50 blend by weight of Asahi Kasei Corporation's styrene-ethylene butylene-styrene block copolymer "TUFTECH" (registered trademark) H1052 (acid value 0 mgCH3ONa / g, styrene ratio 20 mol%) and Asahi Kasei Corporation's maleic anhydride-modified styrene-ethylene butylene-styrene block copolymer "TUFTECH" (registered trademark) M1913 (acid value 10 mgCH3ONa / g, styrene ratio 30 mol%) (average acid value 5 mgCH3ONa / g, average styrene ratio 25 mol%) MahSEBS-5: A blend of Asahi Kasei Corporation's styrene-ethylene butylene-styrene block copolymer "TUFTECH" (registered trademark) H1052 (acid value 0 mgCH3ONa / g, styrene ratio 20 mol%) and Asahi Kasei Corporation's maleic anhydride-modified styrene-ethylene butylene-styrene block copolymer "TUFTECH" (registered trademark) M1913 (acid value 10 mgCH3ONa / g, styrene ratio 30 mol%) in a weight ratio of 80:20 (average acid value 3 mgCH3ONa / g, average styrene ratio 22 mol%) SIBS: Kaneka Corporation styrene-isobutylene-styrene block copolymer "SIBSTAR" (registered trademark) 102T-UC (acid value 0 mgCH3ONa / g, styrene ratio 15 mol%) SEBS-1: Styrene-ethylene-butylene-styrene block copolymer "Tuftec" (registered trademark) H1221 (acid value 0 mgCH3ONa / g, styrene ratio 12 mol%) manufactured by Asahi Kasei Corporation SEBS-2: Styrene-ethylene-butylene-styrene block copolymer "Tuftec" (registered trademark) H1043 (acid value 0 mgCH3ONa / g, styrene ratio 67 mol%) manufactured by Asahi Kasei Corporation

[0048] Preparation of Thermoplastic Resin Composition The raw materials were introduced into a twin-screw kneading extruder (manufactured by Japan Steel Works, Ltd.) with the cylinder temperature set to the melting point of the thermoplastic resin + 20°C, melt-kneaded for a residence time of about 5 minutes, and the molten kneaded material was extruded in a strand shape from a die attached to the discharge port. The obtained strand-shaped extrudate was pelletized with a resin pelletizer to obtain a pellet-shaped thermoplastic resin composition.

[0049] <Measurement of total light transmittance and haze> The pellet-like thermoplastic resin composition was molded into a sheet having an average thickness of 1.0 mm, i.e., a plate-like molded product having a thickness of 1.0 mm, using a 40 mmφ single-screw extruder with a 200 mm wide T-shaped die (Pla Giken Co., Ltd.), with the cylinder and die temperatures set to the melting point of the thermoplastic resin + 20°C, a cooling roll temperature of 50°C, and a take-up speed of 2 m / min. This sheet was cut into a shape of 40 mm x 40 mm to prepare a test piece.

[0050] The total light transmittance (%) and haze (%) of the three test pieces were measured in accordance with JIS K7361-1:1997 and JIS K7136 using a turbidity meter NDH2000 manufactured by Nippon Denshoku Industries Co., Ltd. at 23°C, with a light source of D65, a measuring diameter of 20 mm, and a single beam system, and the average values ​​were calculated.

[0051] The total light transmittance and haze for each example are shown in Tables 1-1 and 1-2.

[0052] <Measurement of oxygen permeability coefficient> The pelletized thermoplastic resin composition was molded into a sheet with an average thickness of 0.2 mm using a 40 mmφ single-screw extruder with a 550 mm wide T-type die (Pla Giken Co., Ltd.) with the cylinder and die temperatures set to the melting point of the material with the highest melting point in the composition + 20°C, a cooling roll temperature of 50°C, and a take-up speed of 3 m / min.

[0053] The sheet was cut to a specified size and measured for oxygen permeability (mm cc / (m)) at 21°C and 0% RH using OXTRAN 1 / 50 manufactured by MOCON in accordance with ASTM D3985. 2 The mean daily Hg (day·mmHg) was calculated.

[0054] The oxygen permeability coefficient in each example is shown in Tables 1-1 and 1-2.

[0055] Measuring Domain Size The pellet-like thermoplastic resin composition was molded into a sheet with an average thickness of 1.0 mm using a 40 mmφ single-screw extruder with a 200 mm wide T-shaped die (Pla Giken Co., Ltd.) with the cylinder and die temperatures set to the melting point of the thermoplastic resin + 20°C, a cooling roll temperature of 50°C, and a take-up speed of 2 m / min. The molded sheet was cut out, and a surface perpendicular to the extrusion direction was made with a razor, and then cooled with liquid nitrogen and a smooth surface was made with a diamond knife.

[0056] This surface was captured as a phase image in tapping mode using an atomic force microscope (AFM MFP3D) manufactured by Asylum Research, with contrast between the matrix and the domains. The image obtained was then binarized, after which particle analysis was performed on approximately 500 domains using image analysis software to determine the number-average particle size (μm).

[0057] The number average particle size (domain particle size) of the domains in each example is shown in Tables 1-1 and 1-2.

[0058] Grain detection and removal of grains from test specimens The pellet-like thermoplastic resin composition was molded into a sheet with an average thickness of 1.0 mm using a 40 mmφ single-screw extruder with a 200 mm wide T-shaped die (Pla Giken Co., Ltd.) under conditions of a cylinder and die temperature set to the melting point of the thermoplastic resin + 20°C, a cooling roll temperature of 50°C, and a take-up speed of 2 m / min. The molded sheet was cut into three flat plates with a width of 80 mm and a length of 150 mm to prepare test pieces.

[0059] The test pieces were observed using an X-ray CT (Yamato Scientific 3D measurement X-ray CT TDM-1300-IS), and the total number of grains with a maximum length of 0.7 mm or more was counted. Next, the test pieces were irradiated with a D65 light source, and the total number of grains with a maximum length of 0.7 mm or more was counted.

[0060] The particle detection rate was calculated as the ratio of the number of particles counted by optical inspection to the number of particles counted by X-ray CT (number of particles counted by optical inspection / number of particles counted by X-ray CT × 100%).

[0061] A grain detection rate of 80% or more was judged as high, 60% to less than 80% as medium, and less than 60% as low.

[0062] The results of the grain detection rate in each example are shown in Tables 1-1 and 1-2.

[0063] Next, for each test piece, the position of the longest grain having a length of 0.7 mm or more was marked when observed by irradiating it with a D65 light source.

[0064] For the test pieces of Examples 1 to 13 and Comparative Examples 1 to 3, 12 test pieces were prepared by punching out into a JIS No. 6 dumbbell shape while avoiding the marked positions, i.e., not including the observed grains, for each of them. For the test piece of Comparative Example 4, 12 test pieces were prepared by punching out into a JIS No. 6 dumbbell shape while including the marked positions, i.e., including the observed grains.

[0065] Constant strain fatigue test A constant strain fatigue test was performed on the dumbbell-shaped test pieces using a 48-strand constant load constant strain fatigue tester manufactured by Ueshima Seisakusho, in accordance with JIS K6270:2018 - Determination of tensile fatigue properties of vulcanized and thermoplastic rubbers. The number of breaks was determined as the number of times that 60% of the 12 test pieces in each example broke. The number of breaks in each example was calculated as an index with the number of breaks in Comparative Example 1 set to 100.

[0066] The fracture surfaces of the broken specimens were observed under an optical microscope to confirm the presence of grains at the fracture site. If grains were found at the fracture site in more than half of the broken specimens, the fracture mode was determined to be "grain origin." If grains were not found at the fracture site in more than half of the broken samples, the fracture mode was determined to be "fatigue fracture."

[0067] The number of domain breaks and the breakage mode for each example are shown in Tables 1-1 and 1-2.

[0068] <result> The conditions and test results for each example are shown in Tables 1-1 and 1-2 below.

[0069] [Table 1-1]

[0070] [Table 1-2]

[0071] The present disclosure includes the following inventions. [Invention 1] A hose for transporting hydrogen, comprising an inner layer, a reinforcing layer, and an outer layer in this order, The inner layer is The thermoplastic resin composition is made of a thermoplastic resin and an elastomer, and has a total light transmittance of 60% or more in a plate-shaped molded product having a thickness of 1.0 mm as measured in accordance with JIS K7361-1:1997; and When observed under light of D65 light source, it does not have particles with a major axis of 0.7 mm or more. A hose for transporting hydrogen, comprising: [Invention 2] 2. The hose for transporting hydrogen according to Invention 1, wherein the thermoplastic resin composition has a haze of 90% or less in a plate-shaped molded product having a thickness of 1.0 mm, as measured in accordance with JIS K7136:2000. [Invention 3] 3. The hose for transporting hydrogen according to Invention 1 or 2, wherein the thermoplastic resin composition has an island-in-a-sea structure in which the thermoplastic resin is a matrix and the elastomer is a domain. [Invention 4] 4. The hose for transporting hydrogen according to Invention 3, wherein the domains have a number average particle size of 1.0 μm or less. [Invention 5] 5. The hose for transporting hydrogen according to any one of Inventions 1 to 4, wherein the elastomer is a modified styrene-based thermoplastic elastomer having a styrene ratio of 15 to 50 mol %. [Invention 6] 6. The hose for transporting hydrogen according to invention 5, wherein the modified styrene-based thermoplastic elastomer is acid-modified and has an acid value of 1 to 15 mgCH3ONa / g. [Invention 7] 7. The hose for transporting hydrogen according to any one of Inventions 1 to 6, wherein 50 mass % or more of the thermoplastic resin is polyamide 11 or polyamide 12. [Invention 8] The oxygen permeability coefficient of the thermoplastic resin composition at 21°C and 0% RH, as measured in accordance with ASTM D3985, is 0.005 to 0.100 mm cc / (m 2 8. The hose for transporting hydrogen according to any one of Inventions 1 to 7, characterized in that the hydrogen transport hose has a resistance of 100% (w / v) to 100% (h / v). [Invention 9] A method for producing a hose for transporting hydrogen, the hose having an inner layer, a reinforcing layer, and an outer layer in this order, comprising the steps of: Molding an inner layer precursor containing a thermoplastic resin composition that contains a thermoplastic resin and an elastomer and has a total light transmittance of 60% or more in a plate-shaped molded product having a thickness of 1.0 mm as measured in accordance with JIS K7361-1:1997; inspecting the inner layer precursor for the presence or absence of particles having a major axis of 0.7 mm or more by a light inspection performed by irradiating the inner layer precursor with light from a D65 light source; removing said particles, if present, from said inner layer precursor; A method for manufacturing a hose for transporting hydrogen, comprising the steps of:

[0072] The hydrogen transport hose of the present invention can be suitably used, for example, as a hose for transporting hydrogen gas from a dispenser installed at a hydrogen station to a fuel cell vehicle or the like. [Explanation of symbols]

[0073] 1. Hydrogen transport hose 2. Inner layer 3 Reinforcement layer 4 Outer layer 5 Layer made of organic fibers 6 Layers made of metal wires

Claims

1. A hose for transporting hydrogen, comprising an inner layer, a reinforcing layer, and an outer layer in this order, The inner layer is The thermoplastic resin composition is made of a thermoplastic resin and an elastomer, and has a total light transmittance of 60% or more in a plate-shaped molded product having a thickness of 1.0 mm as measured in accordance with JIS K7361-1:1997. and When observed under light from a D65 light source, it does not contain particles with a major axis of 0.7 mm or more. A hose for transporting hydrogen, comprising:

2. 2. The hose for transporting hydrogen according to claim 1, wherein the thermoplastic resin composition has a haze of 90% or less in a plate-shaped molded product having a thickness of 1.0 mm, as measured in accordance with JIS K7136:2000.

3. 3. The hose for transporting hydrogen according to claim 1, wherein the thermoplastic resin composition has an island-in-a-sea structure in which the thermoplastic resin is a matrix and the elastomer is a domain.

4. 4. The hose for transporting hydrogen according to claim 3, wherein the number average particle size of the domains is 1.0 μm or less.

5. 3. The hose for transporting hydrogen according to claim 1, wherein the elastomer is a modified styrene-based thermoplastic elastomer having a styrene ratio of 15 to 50 mol %.

6. The modified styrene-based thermoplastic elastomer is acid-modified and has an acid value of 1 to 15 mgCH 3 6. The hose for transporting hydrogen according to claim 5, wherein the hydrogen permeability is 0.1 to 1.0 μm.

7. 3. The hose for transporting hydrogen according to claim 1, wherein 50 mass % or more of the thermoplastic resin is polyamide 11 or polyamide 12.

8. The oxygen permeability coefficient of the thermoplastic resin composition at 21° C. and 0% RH measured in accordance with ASTM D3985 is 0.005 to 0.100 mm·cc / (m 2 3. The hydrogen transport hose according to claim 1, wherein the resistance to flow of the hydrogen is 0.05-0.05 m / s.day-mmHg.

9. A method for producing a hose for transporting hydrogen, the hose having an inner layer, a reinforcing layer, and an outer layer in this order, comprising the steps of: Molding an inner layer precursor containing a thermoplastic resin composition that contains a thermoplastic resin and an elastomer and has a total light transmittance of 60% or more in a plate-shaped molded product having a thickness of 1.0 mm as measured in accordance with JIS K7361-1:1997; inspecting the inner layer precursor for the presence or absence of particles having a major axis of 0.7 mm or more by a light inspection performed by irradiating the inner layer precursor with light from a D65 light source; removing said particles, if present, from said inner layer precursor; A method for producing a hose for transporting hydrogen, comprising the steps of:

Citation Information

Patent Citations

  • Hydrogen transport component

    WO2018155491A1